Pelatihan Content creator dan Video Profesional bagi Siswa SMA/SMK - Sutresno, Stephen Aprius; Suni, Eugenius Kau; Bata, Julius Victor Manuel; Airlangga, Gregorius; Christanto, Henoch Juli; Sihombing, Denny Jean Cross; Piolo, Samuel (Penerbit Goodwood, 2024)
Purpose: This training for social media content creators and professional video production techniques is conducted with the aim of providing motivation and insights into the tricks and techniques needed to become a content creator. The goal is for the participants, who are high school students, to utilize their gadgets and time more constructively rather than for consumptive purposes. Methodology: Organized by the Information Systems Department of Atma Jaya Catholic University of Indonesia, this training will be held at Campus 3 BSD Unika Atma Jaya on Saturday, November 25, 2023. Targeting 60 to 100 high school students from Banten, the activity will be evaluated using pre-tests and post-tests, calculated manually using the average formula. Results: The result of the training activity went smoothly and achieved the initial target of being attended by 90 active participants. The selection of speakers for the training was also appropriate, matching their expertise, and they were able to deliver the material clearly using various real-life examples. The evaluation results of the activity showed that the post-test scores increased by 43.7% compared to the pre-test scores. Therefore, it can be concluded that the participants understood what was conveyed by the speakers. Conclusions: The right resource persons and interactive learning methods contributed to the effectiveness of the training. The success of this activity shows a positive impact in increasing the creativity and productivity of the younger generation in utilizing gadgets constructively. Limitations: Due to time and budget constraints, the activity was not conducted with direct hands-on practice in the form of a workshop. Additionally, the target participants were limited to the surrounding area, specifically high school students in the Banten region. Contribution: This training gives high school students broader insights, enabling them to use their gadgets and time positively. It also equips them to become content creators by learning professional video production and social media management skills.